Desain Penyuntingan On-Line Secara Kolaborasi untuk Peningkatan Hasil Penulisan Karya Ilmiah Dosen - Eka Pramono Adi; Henry Praherdhiono; Yulias Prihatmoko (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2018)
The lecturer community needs a vehicle to construct knowledge in the form of collaborative scientific writing. Managing scientific writing knowledge in a collaborative manner is a major opportunity to achieve significant improvements in the substantial performance of lecturers at the State University of Malang. The concept of Web.2.0 technology with a Wiki and its facilities allows lecturers at the State University of Malang to create, publish and share digital content in new and existing social communities. The aim is to produce a web-based scientific writing collaboration system model between lecturers in the State University of Malang. The development model used is the Davidson-Shivers and Rasmussen (2007) model and is selected based on its suitability to the characteristics of system development.